Training on Making Compost from Training on Making Compost from Household Organic Waste as an Effort for Sustainable Waste Management in Garut Regency - Indra Dodo Saputra; Chevi Ardiana Rusmawan; Diah Ika Putri; Dewi Hernawati; Asep Rohayat (Indonesian Journal of Community Empowerment (IJCE), 2026)
Household organic waste management is one of the main environmental challenges in Indonesia, especially in rural areas with limited access to formal waste processing facilities. This community service activity was carried out in Garut on April 24, 2026, with the aim of increasing public understanding and skills in processing household organic waste into compost. The method used was a workshop combining interactive lectures and hands-on practice demonstrations using a simple composter drum. Participants were members of the local community, primarily housewives. The results showed that participants were highly enthusiastic and gained new knowledge about composting principles, organic waste sorting, and the application of compost as organic fertilizer for home gardens. 90,91% of participants reported that the activity was very beneficial and expressed readiness to independently practice composting at home. Through this activity, it is expected that the community will be able to manage organic waste sustainably, reduce dependence on chemical fertilizers, and minimize environmental pollution.